ANALISIS KINERJA MELALUI PELATIHAN MAHASISWA MAGANG - Sayyida, Ridha Ahda; Arif, Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
All internship students at PT. Bank Sinarmas, Tbk UUS Malang Branch did not reach the specified target. On average, students are only able to get a target of 36%. This is still considered very far from meeting the targets set by PT. Bank Sinarmas, Tbk UUS Malang Branch. The acquisition data that has been disclosed is not in line with the training provided by PT. Bank Sinarmas, Tbk UUS Malang Branch where one of the objectives of the training is so that students are able to meet the targets set by Bank Sinarmas. This research was conducted using a descriptive qualitative approach which was carried out at PT. Bank Sinarmas Tbk Sharia Business Unit Malang Branch in August – October 2022. The subjects in this study consisted of 49 Internship Students in the Independent Campus Independent (MBKM) Non-DIKTI 2021 – 2022 Certified Internship program at PT. Bank Sinarmas Tbk, Sharia Business Unit (UUS) Malang Branch by taking 5 (five) students as samples who were used as informants as an interpretation of the number of working groups. The results of the study stated that the dimensions of quality, quantity, timeliness, independence and commitment in training had a positive impact on improving performance. Meanwhile, the dimensions of training effectiveness do not have a large enough impact on performance.